Human Resources Information Systems: Transactional and Strategic Paradigm - Anton Florian Barišić; Mirjana Pejić Bach; Ivan Miloloža (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Human resources information system (HRIS) is an inevitable element of contemporary organisation's setup. The HRIS provides multiple human resources management (HRM) services from operational assistance in collecting, storing and preparing data, executing and controlling processes, reducing HRM labour costs, and providing information to the management enabling them to make quality HR strategic decisions. This paper is aimed in contributing to the better utilization of HRIS usage in organizations, analysing various approaches in terms of purposefulness and validity of implementation of HRIS with the goal to maximize its impact to organizational performance. The goal of the paper is to provide the overview of HRIS transactional and strategic paradigm, and evaluate its impact to organizational performance.
Keywords: M10; O32; O33; L25; M55; 330; management; human resources; human resources information system; outsourcing; organizational performance